2019
DOI: 10.1371/journal.pone.0217059
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of biological and enzymatic quorum quencher coating additives to reduce biocorrosion of steel

Abstract: Microbial colonization can be detrimental to the integrity of metal surfaces and lead to microbiologically influenced corrosion (MIC). Biocorrosion is a serious problem for aquatic and marine industries in the world. In Minnesota (USA), where this study was conducted, biocorrosion severely affects the maritime transportation industry. The anticorrosion activity of a variety of compounds, including chemical (magnesium peroxide) and biological (surfactin, capsaicin, and gramicidin) molecules were investigated as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 57 publications
1
43
0
Order By: Relevance
“…Also, little is known about the effect of the interference of QS systems on the microbial composition of multispecies biofilms. The use of the QQ enzyme SsoPox as a coating additive was recently reported to significantly decrease biocorrosion in steel coupons after 8 weeks of submersion in water, and this effect was associated with a deep change in the microfouling community [ 28 ]. In the present work, adding the AHL-lactonase Aii20J (0.57 mM) clearly inhibited the mixed biofilms containing the QQ-sensitive P. flavipulchra strain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, little is known about the effect of the interference of QS systems on the microbial composition of multispecies biofilms. The use of the QQ enzyme SsoPox as a coating additive was recently reported to significantly decrease biocorrosion in steel coupons after 8 weeks of submersion in water, and this effect was associated with a deep change in the microfouling community [ 28 ]. In the present work, adding the AHL-lactonase Aii20J (0.57 mM) clearly inhibited the mixed biofilms containing the QQ-sensitive P. flavipulchra strain.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the AHL-lactonase Aii20J has been reported to be active against AHL producers [ 12 , 22 , 23 ], but also against bacterial strains that are not [ 21 ]. Moreover, previous studies indicated that the external addition of QQ enzymes that degrade AHLs into complex biofilm could affect both Gram-negative and Gram-positive bacteria [ 14 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of SsoPox variant in capsules led to changes in bacterial communities and to biofilm inhibition (102). SsoPox W263I immobilized in a silica gel coating painted on steel plates was also able to reduce corrosion tubercles by 50% compared with controls after 8 weeks of immersion in Duluth-Superior Harbor (Minnesota, USA) (103). The use of enzymes instead of or as a complementation to biocides in paint is attractive, due to use restriction of some biocides because of their negative impact on the environment (125).…”
Section: Biofouling/biocorrosionmentioning
confidence: 99%